ОД ПРАКТИКАТА - ИНТЕРВЈУА (Ревија за социјална политика/Journal of Social Policy, 2008)
The social protection system is facing the challenge of new reforms. Social assistance is one of the forms of social support that will soon be subject to certain systemic changes. By valuing the experiences from practice - social workers, as social assistance administrators, as well as beneficiaries of social (monetary) assistance, several focus groups have been made for the needs of the revision in order to emphasize their thoughts and attitudes.